PENINGKATAN KETERAMPILAN PASSING ATAS BOLA MELALUI MODIFIKASI ALAT - Eko Setyo (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
This research is aimed at describing the upgrading of volley ball set up skillthrough equipment modification. The method used in this research is Action Researchby using Kemmis and Mc Taggart model. The result of the research shows there is volleyball set up skill upgrading. This result can be proofed by students’ average percentagewhich is started from pre-cycle is 21,3%, in cycle I rises 53,6% and cycle II becomes85,7%. Therefore, the equipment modification application can help students inupgrading their volley ball set up skill and gives the students stimulation. Thisstimulation should be adapted with the condition of the material being taught. Thismodification can help students in comprehending and practicing volley ball set up skill.Keyword: volleyball set up, equipment modification